India: Development with a human face - Ray, Syamal Kumar (2004)
Calling Globalisation `the central challenge we face today' world leaders present at the United Nations Millennium Summit September 8, 2000 had to recognise that the benefits of globalisation were very unevenly shared and the costs were unevenly distributed despite the fact that it actually offered great opportunities. The present article is addressed to the problem of inequality in the context of reprioritisation of India's development agenda in the era of globalisation under the following four heads: (a) clearing the conceptual deck and setting up the context; (b) the nature and capacity of the state; (c) the fallout of globalisation; and (d) the prognostic part of the discourse. - Reproduced.
Keywords: Good governance - India; Globalization - India; Economic and social development - India; Good governance